Enhanced Performance of InGaN‐Based Blue LEDs Using an AlGaN/InGaN Super‐Lattice Last Quantum Barrier. Issue 16 (20th May 2019) - Hu, Jiahui; Chen, Qian; Long, Hanling; Zhang, Shuang; Gao, Yang; Zheng, Zihua; Chen, Changqing; Zhang, Jun; Dai, Jiangnan
Abstract : In this work, a novel structure of InGaN‐based blue light‐emitting diodes (LEDs) using a super‐lattice structure as the last quantum barrier (QB) in the active region is proposed to improve the blue LEDs performance. The optical power and external quantum efficiency (EQE) are investigated by both simulation and experiment. The proposed super‐lattice last QB can significantly enhance the effective barrier of electrons from 463 to 576 meV in the conduction band and thus block the leakage of electrons. It is found that such structure can also facilitate the hole injection due to the reduced effective barrier height from 293 to 261 meV in the valance band. Eventually, the increase of the carrier concentration in the active region further improves the internal quantum efficiency (IQE) of the device. The experimental results indicate that the output power of the proposed LED is increased by 16.9% compared with the conventional LED, with lower efficiency droop (less than 20.65%). The proposed structure can be an alternative in pursuing high efficiency blue LEDs in the future. Abstract : Conventional last quantum barrier is replaced by the super‐lattice structures to obtaining better hole injection efficiency, thus enhance the luminescent performance of InGaN‐based light‐emitting diodes.